Synthesis of graphene oxide (GO) and reduced graphene oxide (rGO) and their application as nano-fillers to improve the physical and mechanical properties of medium density fiberboard - Gul, Waheed; Akbar Shah, Syed Riaz; Khan, Afzal; Ahmad, Naveed; Ahmed, Sheraz; Ain, Noor; Mehmood, Arshad; Salah, Bashir; Ullah, Syed Sajid; Khan, Razaullah (Frontiers in Materials, 2023)
Graphene is one of the advanced materials lies in the group of carbon and offers greater mechanical, electrical, structural and optical properties. In order to enhance the physiomechanical characteristics of medium-density fiberboard, the synthesis, characterization, and special effects of graphene oxide (GO) and reduced graphene oxide (rGO) nanoparticles were carried out (MDF). At dosing (1.0, 2.0, and 3.0 wt%), graphene oxide (GO) and reduced graphene oxide (rGO) nanoparticles were incorporated into urea-formaldehyde (UF) resin. In order to manufacture MDF, the Nano fillers were created by being sonicated and combined with natural wood fibers. In order to observe the behavior of nanoparticles in Nano fillers, microstructure characterizations were conducted. The manufactured Nano MDF samples underwent physical and mechanical testing. When 1-3% of nanoparticles were added to the urea-formaldehyde resin, there was a noticeable improvement in mechanical characteristics, namely in the modulus of rupture (MoR) and internal bonding (IB). Additionally, results demonstrated a significant improvement in water absorption and thickness swelling (Ts) (WA). Additionally, the use of Go and rGO nanoparticles significantly shortened the urea formaldehyde resin's curing time and increased its thermal stability. Compared to GO, rGO impacts Nano MDF and enhances all mechanical and physical qualities. Nano MDF and improved all physical and mechanical properties better than GO.